Effervescent Tablet Formulation for Appetite Stimulation with Extracts of Temulawak, Pegagan, Lempuyang Wangi, and Sweet Fennel - Sugito, Esther Shirley; Sulastri, Titin; Suwitono, Marvel Reuben (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The study develops an effervescent tablet formulation with a combination of extracts from temulawak, pegagan, lempuyang wangi, and sweet fennel to increase appetite. Such underweight conditions always lead to a lot of health burdens, like a poor immune system and stunted growth, which makes it highly relevant to have an effective appetite stimulant. The aim of this study is to test the acceptability and effectiveness of the sweeteners (i.e., cane sugar, stevia, and maltodextrin) used in the tablets. The results indicate that all tablet formulations (F1, F2, and F3) passed the granule and physical tablet tests, demonstrating that all variants are of good quality. Moreover, the well-structured formulation process and selection of ingredients in their natural form make the product safe for consumption and effective, hence a really good alternative for improving one's appetite naturally. The present study provides evidence for the role that potentially existing herbal remedies from traditional knowledge may play in their modern applications, nutraceuticals, and improved public health via a simple and effortless means of stimulating appetite.